Sabah castor (ricinus communis linn) maturity stages based on oil content and fruit development changes - Hilarion, C.C.C.; Jupikely James Silip; Atong, M.; Mohamadu Boyie Jalloh; Jualang @Azlan Abdullah Gansau (2015)
Castor is an important oilseed crop with indeterminate maturity due to its indeterminate growth habit. The flowering and fruiting of castor in the same raceme do not occurred at the same time (David et al., 2013). In addition, successive generations of racemes continues to sprout before the primary raceme enter full maturity stage resulting in the existence of mature racemes, immature racemes and flowering raceme (Baldanzi et al., 2002; Vallejos et al., 2011; David et al., 2013). The indeterminate maturity of castor causes difficulty in determining whole raceme maturity making it hard to decide the optimum harvest time for castors.